Association between functional dentition and ultra-processed food consumption in Brazilian adults: A cross-sectional study. - Orlando Luiz do Amaral Junior; Maria Laura Braccini Fagundes; Augusto Bacelo Bidinotto; Matheus Neves; Fernando Neves Hugo; Jessye Melgarejo do Amaral Giordani (PLoS ONE, 2025)
Objective This study aimed to verify if there is an association between functional dentition and ultra-processed diet in Brazilian adults. Methods This cross-sectional study used data from the National Health Survey (PNS) 2019. For the present study, we included only adults aged 18-49 (n = 50,146). The outcome was the ultra-processed food consumption score, calculated based on the sum of positive responses regarding the consumption of 10 subgroups of ultra-processed foods on the previous day. These subgroups represent foods widely consumed in Brazil, and the scoring method has been previously validated for this purpose. The main predictor used was the variable 'functional dentition', categorized into individuals with less than 20 teeth and individuals with 20 or more teeth (functional dentition). Multivariate analysis was performed using the Poisson regression model with robust variance to estimate crude and adjusted prevalence ratios (PR). Results It was observed that the presence of functional dentition (20 or more teeth) was not associated with a greater consumption of an ultra-processed diet (RP = 0.97 [95% CI: 0.91-1.05]), p = 0.578). Conclusion The lack of a significant association between functional dentition and ultra-processed foods consumption suggests that social determinants might play a more important role in shaping dietary habits. The implementation of public policies that promote equitable access to healthy foods and preventive oral health care could contribute to overall health improvements and inequalities reduction.